2013
DOI: 10.1073/pnas.1218765110
|View full text |Cite
|
Sign up to set email alerts
|

AMPA receptor/TARP stoichiometry visualized by single-molecule subunit counting

Abstract: Members of the transmembrane AMPA receptor-regulatory protein (TARP) family modulate AMPA receptor (AMPA-R) trafficking and function. AMPA-Rs consist of four pore-forming subunits. Previous studies show that TARPs are an integral part of the AMPA-R complex, acting as accessory subunits for mature receptors in vivo. The TARP/AMPA-R stoichiometry was previously measured indirectly and found to be variable and dependent on TARP expression level, with at most four TARPs associated with each AMPA-R complex. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(79 citation statements)
references
References 45 publications
(95 reference statements)
3
75
1
Order By: Relevance
“…We subsequently confirmed that the stoichiometry of the Kv4.2⅐KChIP4 complex affects the properties of Kv4.2 by using tandem repeat constructs in which the stoichiometry is strictly controlled. We finally applied the subunit-counting method by single-molecule imaging (31)(32)(33)(34)(35). Although KChIP4 is a cytoplasmic protein, we could successfully apply the method to determine the number of KChIP4 subunits included in a Kv4.2⅐KChIP4 complex and confirmed that the stoichiometry changes depending on the expression level of KChIP4.…”
Section: Dase-like Protein Kchip Is a Cytoplasmic Protein And Increamentioning
confidence: 82%
“…We subsequently confirmed that the stoichiometry of the Kv4.2⅐KChIP4 complex affects the properties of Kv4.2 by using tandem repeat constructs in which the stoichiometry is strictly controlled. We finally applied the subunit-counting method by single-molecule imaging (31)(32)(33)(34)(35). Although KChIP4 is a cytoplasmic protein, we could successfully apply the method to determine the number of KChIP4 subunits included in a Kv4.2⅐KChIP4 complex and confirmed that the stoichiometry changes depending on the expression level of KChIP4.…”
Section: Dase-like Protein Kchip Is a Cytoplasmic Protein And Increamentioning
confidence: 82%
“…TARP proteins have not been crystallized, but the intracellular tail (N ϭ ϳ120 amino acids) of the most studied TARP representative Stargazin is estimated to be ϳ3 nm in radius assuming an unstructured globule, as calculated from the radius of gyration of a ran- et al, 2004), where N is the number of amino acids and b is a constant that is a function of the persistent length of the polymer. Given the residue count of GluK2 cytoplasmic portion is intermediate between that of GluA1 and that of GluA2 and that full AMPARs can contain anywhere from 1 to 4 Stargazin subunits (Hastie et al, 2013), we conservatively modeled the intracellular radius of the AMPAR complex to be 8 nm. The radii of adhesion molecules were taken from a random distribution ranging from 3 to 8 nm.…”
Section: For Simulationsmentioning
confidence: 99%
“…Divalent PDZ-binding interactions within the synapse can stabilize the mobility of transmembrane proteins more than monovalent interactions can AMPA receptors could bear multiple TARPs capable of binding PSD scaffold molecules (Hastie et al, 2013). To test the role of divalent receptor-scaffold interactions on receptor mobility in the synapse, we developed a chemically inducible heterodimerization strategy that would permit us to acutely convert our typical monovalent binding probe to one with divalent PDZ-binding capacity.…”
Section: Intracellular Protein Bulk Can Influence the Synaptic Mobilimentioning
confidence: 99%
“…Fourth, we show that the long extracellular loop 1 of g8 is a very strong positive modulator of AMPA receptor gating, whose influence is likely held in check by the substoichiometric combination of g8 with the AMPA receptor (Hastie et al, 2013). The subunit g8 slows receptor desensitization via L1.…”
Section: Discussionmentioning
confidence: 76%
“…On the other hand, some studies of assembly made use of functional tests to assess the strength of interaction (Shi et al, 2009). Given the variable stoichiometry of assembly between different TARP isoforms (Kim et al, 2010;Hastie et al, 2013), interpreting these data, which combine the strength of association, expression and modulation into a single metric, is difficult. Very recently, a chimeric approach confirmed impressions from structural studies that transmembrane interactions are important for proper assembly, with the TM3 and TM4 segments of g2 and the M1-M3 helices of the AMPA receptor determining complex assembly.…”
Section: Introductionmentioning
confidence: 99%